Analysis of company characteristics and deferred tax burden using profit management detection methods - Maya Macia Sari; Ika Nurhaliza; Pebrilia Amanda Hada; Tahany Syade; Yogi Purwanto (Universitas Pendidikan Nasional, 2023)
This article delved into the intricate relationship between company characteristics and the manipulation of deferred tax burdens, employing profit management detection methodologies. Through various analytical approaches such as qualitative examination of corporate policies, historical scrutiny, and statistical techniques to identify irregularities in financial statements, we investigated patterns indicative of potential financial manipulation, particularly concerning the handling of deferred tax burdens. Our research shed light on the factors influencing a company's decision-making regarding deferred tax burdens and their implications for profit management strategies. By employing profit management detection methods, typically utilized to scrutinize financial statement integrity, including the treatment of deferred tax burdens, our study aimed to unveil the intricate dynamics between company attributes and the management of tax-related liabilities. This investigation not only contributed to the understanding of financial reporting practices but also offered valuable insights for stakeholders, regulators, and investors seeking to comprehend the nexus between company characteristics and the manipulation of deferred tax burdens within the realm of profit management.